Dynamic links among tourism, energy consumption, and economic growth: Empirical evidences from top tourist destination countries in Asia. Issue 4 (1st February 2021) - Azam, Muhammad; Abdullah, Hussin
Abstract : Achieving sustainable development is the prime objective of every government. Based on Solow's theoretical proposition, this study attempts to explore empirically the linkages between tourism, energy consumption, and economic growth, for the top nine Asian travel and tourism countries including Indonesia between 1995 and 2018. The fully modified ordinary least squares method and Granger's causality approaches are implemented for empirical analysis. The empirical result reveals that tourism has a statistically positive impact on economic growth in Asia's top nine travel and tourist countries. Moreover, energy consumption, exports, and savings have also a positive and statistically significant impact on economic growth. The results of panel Granger causality tests demonstrate that there is a mutual interdependence between tourism, energy consumption, and economic growth in the selected panel country group. The empirical finding indicates the positive influences of tourism on economic growth; therefore, the government must strive to formulate a policy that would help to build infrastructural adequacy and promote tourism development in Asian countries.